PENGARUH PERMINTAAN KREDIT TERHADAP PERTUMBUHAN EKONOMI DENGAN INTERAKSI KEBIJAKAN MONETER DI SULAWESI SELATAN - Nurmala Dewi; M. Wahyuddin Abdullah (Universitas Islam Negeri Alauddin Makassar, 2018)
This study aims to examine the effect of credit demand on economic growth with the interaction of monetary policy in South Sulawesi. Variables used in this research are working capital credit, investment credit and consumer credit as independent variable, economic growth as dependent variable and monetary policy as moderation variable. The type of research used in this study is the type of quantitative research. The analysis technique used is multiple linear regression. The result of research with multiple linear regression analysis shows that (1) Credit has positive and significant effect to economic growth in South Sulawesi period 2005-2014. The analysis of the moderating variable with the approach of the absolute difference value indicates that the variable (2) Monetary policy (interest rate) is not enough to strengthen the interaction between working capital loan and investment credit to economic growth. (3) Analysis of moderating variable with approach of absolute difference value indicates that monetary policy variable (interest rate) able to strengthen interaction between consumer credit to economic growth.